2019
DOI: 10.3397/1/376745
|View full text |Cite
|
Sign up to set email alerts
|

Vibration suppression of railway vehicles using a magneto-rheological fluid damper and semi-active virtual tuned mass damper control

Abstract: A semi-active virtual tuned mass damper (SAVTMD) control algorithm is developed to suppress vibrations of a railway vehicle by using magneto-rheological (MR) damper. To this end, a virtual-tuned-mass-damper control algorithm analogous to the tuned mass damper was developed prior to the semi-active application. The proposed SAVTMD control algorithm uses the acceleration of the car body directly, so that it is more practical than the sky-hook control algorithm that uses the velocity of the car body. The applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…in which, m a is the gain that can be thought of as the mass of the virtual tuned mass damper, ζ a is the damping factor of the VTMD controller that is generally set to 0.3 to provide reasonable control bandwidth, and ω a is the filter frequency of the VTMD controller that is normally tuned to either the driving frequency, or the natural frequency of the primary structure. Shin et al 13 found that the control algorithm expressed by equation ( 2) exactly emulates the dynamic characteristics of the tuned mass damper shown in Figure 2. The VTMD controller amounts to attaching a passive TMD to the primary mass, as shown in Figure 2.…”
Section: Single-input Single-output Virtual Tuned Mass Damper Controlmentioning
confidence: 96%
See 3 more Smart Citations
“…in which, m a is the gain that can be thought of as the mass of the virtual tuned mass damper, ζ a is the damping factor of the VTMD controller that is generally set to 0.3 to provide reasonable control bandwidth, and ω a is the filter frequency of the VTMD controller that is normally tuned to either the driving frequency, or the natural frequency of the primary structure. Shin et al 13 found that the control algorithm expressed by equation ( 2) exactly emulates the dynamic characteristics of the tuned mass damper shown in Figure 2. The VTMD controller amounts to attaching a passive TMD to the primary mass, as shown in Figure 2.…”
Section: Single-input Single-output Virtual Tuned Mass Damper Controlmentioning
confidence: 96%
“…Considering that the most popular sensor for vibration measurement is an accelerometer, Shin et al 13 proposed the SISO Virtual Tuned Mass Damper (VTMD) control that is expressed by equation ( 2)…”
Section: Single-input Single-output Virtual Tuned Mass Damper Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in [97] the VATMD is exploited to suppress the self-excited vibration that arises between the girder and magnetic levitation vehicles by performing an active antiresonance assignment through an electromagnetic control force; numerical simulations corroborate the effectiveness of the technique. The semi-active TMD using a magneto-rheological fluid damper for controlling the vibration of railway vehicles is proposed in [98] with an experimental application.…”
Section: Antiresonance Assignment In Buildings and Civil Structuresmentioning
confidence: 99%